Ask the parents: Testing the acceptability and usability of a hypospadias decision aid. Issue 2 (April 2022) - Binion, Kelsey; Miller, Andrew; Misseri, Rosalia; Kaefer, Martin; Longtin, Krista; Carroll, Aaron; Wiehe, Sarah E.; Chan, Katherine H.
Summary: Introduction: In previous work, we engaged key stakeholders to create a web-based decision aid (DA) prototype to facilitate shared decision making about hypospadias. Objective: The study's objective was to use a human-centered design approach to assess the DA's acceptability and usability and revise it prior to pilot testing. Methods: We recruited English-speaking parents (≥18 years old) of sons with hypospadias (≤5 years) for a two-phase process of semi-structured phone/video interviews to obtain feedback about our DA prototype. DA webpages included: "Hypospadias, " "Surgery Basics, " "No Surgery, " "Family Stories, " "Help Me Decide, " and "FAQs." In both phases, participants viewed the DA using the "think aloud" technique and completed several validated scales to evaluate its acceptability and usability. In phase 1, we collected feedback about the "Homepage" organization, values clarification methods (VCM), and webpage content. In phase 2, participants searched the DA for answers to hypospadias-related questions, provided feedback on testimonial videos and VCM, and shared their preferences about data visualizations. All interviews were audio recorded. After each phase, transcripts were qualitatively analyzed to identify key areas for revision. Revisions were made between phase 1 and 2 to improve the DA's acceptability and usability. Results: We interviewed 20 participants (10/phase): median age 33.7 years, 60% female, 80% White. Mean score on the Preparation for Decision Making Scale: 86.8 (out of 100). We revised: 1) VCM, focusing on pros/cons of surgery and question prompts, 2) "Homepage, " adding webpage descriptions (Extended Summary Figure), 3) menu organization, 4) "Surgery Day" webpage, adding general anesthesia risk information, and 5) "Hypospadias" webpage, adding an icon bar graph to help participants visualize statistics. Participants thought the testimonial videos were relatable and the VCMs would prepare them for their visit with their child's urologist. Discussion: Ours is the first parent-centered DA developed and pre-tested for hypospadias. Using validated usability and acceptability scales, participants highly rated the DA in helping them arrive at a decision about surgery. Study limitations include the sample's lack of diversity (i.e., educated, health literate) and participants already decided about their son's hypospadias management before enrolling. To learn more about the DA's usability and acceptability, we plan to pilot test it in a clinical setting. Conclusions: Participants found our DA informative in understanding hypospadias. There was a high perceived level of preparation for hypospadias decision making. Participatory research methods, such as "think aloud, " may be helpful when testing DAs as they privilege the patient's experience. Summary Figure "Homepage" revisions based on participant feedback. Note . The illustration on the left is the "Homepage, " which was tested in phase 1. Using the feedback from phase 1, we reorganized the homepage, included webpage descriptions, and defined hypospadias more distinctively. Summary Figure